Selection of a New Highly Resistant Strain for Malolactic Fermentation under Difficult Conditions - Guzzon, R.; Poznanski, E.; Conterno, L.; Vagnoli, P.; Krieger-Weber, S.; Cavazza, A. (South African Journal of Enology and Viticulture, 2016)
Malolactic fermentation (MLF) is a biological process that contributes to wine quality, but it is frequently affected by various vinification conditions. Resistance to four wine-limiting factors was studied with respect to 10 Oenococcus oeni strains in order to select a suitable strain for performing reliable MLF in difficult wines. Resistance to low fermentation temperature, high SO2 and/or ethanol concentration, and low pH were assayed in laboratory tests. A pool of the most resistant strains was used in a set of laboratory MLFs. At the end of fermentation, the dominant strains were identified by RAPD-PCR. The PN4 strain was found to be dominant in the majority of cases and under the most detrimental wine conditions, and it was therefore chosen as the single-strain inoculum for the subsequent MLF trials. The effectiveness of the PN4 strain was confirmed in a series of MLFs carried out in three different countries under experimental and industrial conditions. It accomplished MLF in wines with up to 15.8% ethanol, pH as low as 3.0, 60 mg/L of free SO2, and in fermentation temperatures below 17ºC. Our findings indicate that the O. oeni PN4 strain could be an effective starter, guaranteeing regular and reliable MLF fermentation.